Regional workshop on East Africa's agricultural information needs - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
The third in a series of four regional workshops on Africa's information needs was held in Mahe, Seychelles, in December 1993